The circuit rider - Eggleston, Edward, 1837-1902 (Salt Lake City, UT : Project Gutenberg, 2024)
"The Circuit Rider: A Tale of the Heroic Age" by Edward Eggleston is a novel written in the late 19th century. The story unfolds in a rustic frontier setting, focusing on the early circuit preachers who played a vital role in shaping communities during a chaotic time. The main character, Morton Goodwin, finds himself entangled in romantic interests and local conflicts, particularly involving the spirited Patty Lumsden and her domineering father, Captain Lumsden. At the start of the book, the tale begins with a vivid depiction of a corn-shucking event at Captain Lumsden's farm, capturing the lively social customs of the time. As neighbors gather for the occasion, the dynamic between the characters is established, showcasing Morton's admiration for Patty and his competitive spirit against Bill McConkey. However, tensions rise as Morton grapples with the oppressive influence of Captain Lumsden, who exerts significant control in the settlement and appears determined to thwart Morton's pursuit of Patty. This prelude sets the stage for a narrative filled with both humor and poignant moments of personal conflict against the backdrop of a developing frontier society. (This is an automatically generated summary.)
"Originally appeared as a serial in The Christian Union"--Preface footnote.
Release date is 2024-12-05
Al Haines
Keywords: Social problems -- Fiction; Christian fiction; Circuit riders -- Fiction; West (U.S.) -- History -- 19th century -- Fiction